Anti-Hyperalgesic Properties of Menthol and Pulegone - Hilfiger, Louis; Triaux, Zélie; Marcic, Christophe; Héberlé, Eléa; Emhemmed, Fathi; Darbon, Pascal; Marchioni, Eric; Petitjean, Hugues; Charlet, Alexandre (Frontiers in Pharmacology, 2021)
Context: Menthol, the main monoterpene found in Mentha piperita L. (M. piperita) is known to modulate nociceptive threshold and is present in different curative preparations that reduce sensory hypersensitivities in pain conditions. While for pulegone, a menthol-like monoterpene, only a limited number of studies focus on its putative analgesic effects, pulegone is the most abundant monoterpene present in Calamintha nepeta (L.) Savi (C. nepeta), a plant of the Lamiaceae family used in traditional medicine to alleviate rheumatic disorders, which counts amongst chronic inflammatory diseases. Objectives: Here, we analyzed the monoterpenes composition of C. nepeta and M. piperita. We then compared the putative anti-hyperalgesic effects of the main monoterpenes found, menthol and pulegone, in acute inflammatory pain conditions. Methods:C. nepeta and M. piperita extracts were obtained through pressurized liquid extraction and analyzed by gas chromatography-mass spectrometry. The in vitro anti-inflammatory activity of menthol or pulegone was evaluated by measuring the secretion of the tumour necrosis factor alpha (TNF α) from LPS-stimulated THP-1 cells. The in vivo anti-hyperalgesic effects of menthol and pulegone were tested on a rat inflammatory pain model. Results: Pulegone and menthol are the most abundant monoterpene found in C. nepeta (49.41%) and M. piperita (42.85%) extracts, respectively. In vitro, both pulegone and menthol act as strong anti-inflammatory molecules, with EC50 values of 1.2 ± 0.2 and 1.5 ± 0.1 mM, respectively, and exert cytotoxicity with EC50 values of 6.6 ± 0.3 and 3.5 ± 0.2 mM, respectively. In vivo, 100 mg/kg pulegone exerts a transient anti-hyperalgesic effect on both mechanical (pulegone: 274.25 ± 68.89 g, n = 8; vehicle: 160.88 ± 35.17 g, n = 8, p < 0.0001), thermal heat (pulegone: 4.09 ± 0.62 s, n = 8; vehicle: 2.25 ± 0.34 s, n = 8, p < 0.0001), and cold (pulegone: 2.25 ± 1.28 score, n = 8; vehicle: 4.75 ± 1.04 score, n = 8, p = 0.0003). In a similar way, 100 mg/kg menthol exerts a transient anti-hyperalgesic effect on both mechanical (mechanical: menthol: 281.63 ± 45.52 g, n = 8; vehicle: 166.25 ± 35.4 g, n = 8, p < 0.0001) and thermal heat (menthol: 3.65 ± 0.88 s, n = 8; vehicle: 2.19 ± 0.26 s, n = 8, <0.0001). Conclusion: Here, we show that both pulegone and menthol are anti-inflammatory and anti-hyperalgesic monoterpenes. These results might open the path towards new compound mixes to alleviate the pain sensation.